NATURAL SPACE Conceptual sphere in Ukrainian poetry of the early 21st Century - Петренко, Людмила Олександрівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2020)
The article explores the features of the embodiment of the conceptual sphere NATURAL SPACE in Ukrainian poetry of the early XXI century. defines its composition, describes the semantic structure of conceptual components, characterizes the means of their artistic embodiment in terms of the Ukrainian poetic word usage traditions and highlighting authorship origins.Source for this article was poetry of the modern Ukrainian authors, in particular L. Beley, Y. Izdryk, V. Kalashnyk, M. Kiyanovska, S. Osoka, S. Tatchyn, H. Yanovska and many others. It is emphasized that the composition and structure of artistic conceptual spheres are related to the nature of poetry: artists use common cultural language codes, but try to go beyond them, so the author's forms are recognizable, but not the same as commonly used (forms). SPACE conceptual sphere is one of the main ones in the Ukrainian poetry of the beginning of the XXI century. Its component is NATURAL SPACE conceptual sphere. In Ukrainian poetry of the early XXI century represented by concepts that embody horizontal, vertical and water space, the main among which are FOREST, GARDEN, FIELD, STEPPE, RIVER, SKY. Their verbalizers reflect both traditional associations and encoded authorial meanings.The word forest, on the one hand, as the embodiment of alien space acquires a negative assessment, on the other is positive, has the life meaning. The garden is personal space, so it’s image appears as positive to convey the meaning of the living space of the lyrical hero. This semantics is expressed by Biblical allusions to the Garden of Eden. Similarly, the form of the field, mostly contain the ‘own’ meaning, but at the same time are able to develop the semantics of death. The traditional form of the steppe as freedom is also able to express anxious emotional conditions through a sign of infinity. The sky is a sacred space, an inaccessible place and at the same time a living space of a person, freedom, a sign of “borderline”, embodied, in particular, in the forms of the horizon, is relevant for the expression of temporal semantics. Concepts that embody water space convey the traditional ambivalent meanings of vitality, timeline and danger.